Associated factors for admission among acute exacerbation of chronic obstructive pulmonary disease patients presenting at the emergency department of a tertiary care center in Eastern Nepal: a cross-sectional study - Shrestha, Grishma (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: The burden of COPD continues to increase over the years. COPD exacerbations require frequent hospitalizations and accelerate the decline of lung function. Hence, it is significant to understand the factors that can predict hospitalization due to acute exacerbation of COPD. Method: A cross sectional study was conducted for a period of one year in total of 99 cases with an aim to identify factors associated with hospitalization due to acute exacerbation of COPD in patients visiting emergency department of BPKIHS, eastern Nepal. We obtained data of sociodemographic, clinical, and biochemical parameters. We analyzed their association with hospital admission with a multivariate analysis using a logistic regression model. Result: Among 99 cases 50 were admitted and 49 were discharged. In multivariate analysis, the significant factors predictive of hospital admission in COPD exacerbations were domiciliary oxygen (OR 0.162, 95% CI 0.977-1.138), SpO2 with O2 (OR 0.864, 95% CI 0.146-0.864), neutrophil count (OR 1.274, 95% CI 1.045-1.554), lymphocyte count (OR 1.297, 95% CI 1.027-1.639) and serum urea level (OR 1.045, 95% CI 1.003-1.089). Conclusion: In patients presenting to the emergency department with acute exacerbation of COPD, if the value of any one of the predicting factors (domiciliary oxygen, SpO2 with O2, neutrophil count, lymphocyte count and serum urea level) deteriorates by one unit, then there is 1.420 times increase in hospital admission.